Baropsychology - Sanjay Kalra; Amandeep Singh; Madhur Verma; Nitin Kapoor (Journal of the Pakistan Medical Association, 2026)
Baropsychology may be defined as the study of psychological or emotional causative, contributory and confounding factors, comorbid conditions, and complications of overweight/obesity, as well as the psychological and behavioural interventions used as part of corrective and curative therapy. This brief communication defines, describes and details the concept of baropsychology. It attempts to bring together the various psychosocial and person-centred aspects of obesity care under a single umbrella. This will help ensure focussed and fruitful application of these principles in clinical practice bariatric. Keywords: Obesity, overweight, psychology, psychosocial.